Dental pain associated with untreated dental caries and sociodemographic factors in 5-year-old children - Paredes, Suyene-de Oliveira (J Clin Exp Dent, 2021)
BACKGROUND: The aim of this study was to assess the prevalence of dental pain and to examine its association with untreated dental caries in 5-year-old children. MATERIAL AND METHODS: This was a cross-sectional study of 261 5-year-old children in Northeast Brazil. Parents answered questions about their socioeconomic conditions and their children’s toothache. Trained dentists assessed dental caries using the decayed, missing and filled teeth (dmf-t) index. Binary logistic regression models were used to estimate the unadjusted and adjusted odds ratios (ORs) and the confidence intervals (95% CIs) for the association of dental pain with covariates. The significance level was set at five percent. RESULTS: The prevalence of dental pain was 28.7%, and 48.2% of children had untreated dental caries. Dental pain was associated with untreated dental caries (OR=5.7; 95% CI: 3.1-10.53; p<0.001) and living with one parent or other family members (OR=2.3; 95% CI: 1.2-4.4; p=0.008). Sociodemographic factors were not associated with dental pain. CONCLUSIONS: The prevalence of dental pain in preschool children is high, and this condition is associated with both untreated dental caries and living with one parent or other family members. Key words:Toothache, socioeconomic factors, dental caries.